Development of Ethnomathematics-based Comics on Number Pattern Material - Fakhriyah, Fitri Nur; Merliza, Pika (Unnes Journal of Mathematics Education, 2024)
This study explains the steps in developing mathematical comics and the practicality of using comics in learning mathematics for junior high school students. The aim of this research is to create ethnomathematics-based comic learning media that focuses on number pattern material. The method in this research was the development method (Research and Development) with a 4D model (Define, Design, Develop, Disseminate). The research subjects were 28 class VIII junior high school students. Data collection techniques were carried out through interviews, observation, and questionnaires. The research results showed an average of 92.11% with a validity test score by material experts of 91.34%, while for media experts it was 95% and products that had been validated were then tested on students with results of 90%. Based on the assessment of instructional quality in trials with students, learning media was also stated to be in the very practical category, so that learning media can be used to help the mathematics learning process in schools.